Diversity and Population Density of Nematodes in Melons in Bengkulu City - Djamilah Djamilah; Sempurna Br. Ginting; Priyatiningsih Priyatiningsih; Aris Putra (Badan Penerbitan Fakultas Pertanian (BPFP), 2023)
Melon is one of the horticultural commodities with relatively high economic value and is profitable to cultivate as a source of income for farmers. With the increasing demand for melons, melons are widely cultivated in Bengkulu. Pests and diseases are one of the most disturbing problems in melon cultivation. Plant parasitic nematodes are one of the pests of melon plants that are not paid enough attention to by farmers due to a lack of knowledge about nematodes. Losses caused by nematode attacks on melon plants resulted in decreased production. Information about the types of nematodes is crucial to design an effective control strategy. This study aims to identify the diversity and density of nematode populations on melon plants in the city of Bengkulu. Observation of nematode attacks was carried out directly by observing all parts of the melon plant, especially the roots, and identifying and counting nematode populations. Observation parameters included attack symptoms, types of nematodes, and nematode population densities. This research has been carried out with the results: Symptoms of attack on the ground: stunted plants, languishing, quickly wilted. The symptoms of attack in the soil: Root galls, root wounds, and root rot. There are four types of nematodes, namely Genus: Paratylenchus sp, Meloidogyne spp., Rotylenchulus sp., and Helicotylenchus sp., Paratylenchus sp. population density 131.6; Meloidogyne spp. 86.5 Rotylenchulus sp. 69.7 and Helicotylenchus sp. 47.8.